2010
DOI: 10.1128/jb.00747-10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Intact Surface Layer of Caulobacter crescentus by Cryo-Electron Tomography

Abstract: The surface layers (S layers) of those bacteria and archaea that elaborate these crystalline structures have been studied for 40 years. However, most structural analysis has been based on electron microscopy of negatively stained S-layer fragments separated from cells, which can introduce staining artifacts and allow rearrangement of structures prone to self-assemble. We present a quantitative analysis of the structure and organization of the S layer on intact growing cells of the Gram-negative bacterium Caulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 47 publications
5
45
0
Order By: Relevance
“…The proteinaceous barrier was previously suggested to substitute for other classical Gram-negative cell features, such as cell surface protection more typically provided by O antigen (20), a rigid structural framework in place of peptidoglycan (13), and possibly as an attachment platform for degradative enzymes, as in a related species, Rhodopirellula baltica (21). The proteinaceous exterior of G. obscuriglobus has not been shown to constitute a surface layer (S-layer), typically composed of only one or two proteins in a lattice configuration, like that found in some other bacteria, including archaea and the planctomycete "Candidatus Kuenenia stuttgartiensis" (13,22,23). The original cell wall analysis of G. obscuriglobus by Stackebrandt et al (18) found the cell wall composition to include many amino acids, and the ability of the G. obscuriglobus cell to maintain its integrity was demonstrated by the finding that cell sacculi retained their native cell morphology after 10% SDS treatment (18), thus exhibiting resistance to SDS that is more like that of cells that have a peptidoglycan-containing murein sacculus (21).…”
mentioning
confidence: 99%
“…The proteinaceous barrier was previously suggested to substitute for other classical Gram-negative cell features, such as cell surface protection more typically provided by O antigen (20), a rigid structural framework in place of peptidoglycan (13), and possibly as an attachment platform for degradative enzymes, as in a related species, Rhodopirellula baltica (21). The proteinaceous exterior of G. obscuriglobus has not been shown to constitute a surface layer (S-layer), typically composed of only one or two proteins in a lattice configuration, like that found in some other bacteria, including archaea and the planctomycete "Candidatus Kuenenia stuttgartiensis" (13,22,23). The original cell wall analysis of G. obscuriglobus by Stackebrandt et al (18) found the cell wall composition to include many amino acids, and the ability of the G. obscuriglobus cell to maintain its integrity was demonstrated by the finding that cell sacculi retained their native cell morphology after 10% SDS treatment (18), thus exhibiting resistance to SDS that is more like that of cells that have a peptidoglycan-containing murein sacculus (21).…”
mentioning
confidence: 99%
“…The amino acid sequence specified for each segment is indicated in the supplemental material. The resulting plasmids were introduced by electroporation into JS1023, a C. crescentus NA1000 derivative (25).…”
Section: Methodsmentioning
confidence: 99%
“…Negative staining, thinsection EM Smit et al (1992) Cryo-electron tomography (Cryo-ET) and statistical image processing Amat et al (2010) Arbing) appear to have the self-assembling or "crystallization domain" located in the Cterminal part of the protein, preceded by the cell-wall-anchoring domain(s), mostly SLH domains, at the N-terminus. The SLH domains are present in the majority of bacterial SLPs, though there are exceptions like SbsC in G. stearothermophilus (Pavkov et al 2008).…”
Section: Caulobacter Crescentusmentioning
confidence: 99%